2001
DOI: 10.1111/j.1349-7006.2001.tb01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Involvement of Cell Cycle Arrest and Apoptosis Strengthen the Effect of FTY720

Abstract: A novel reagent, FTY720 (2-amino-2-[2-(4-octylphenyl)ethyl]-1,3-propanediol hydrochloride), has been shown to induce a significant decrease of lymphocytes and lymphoma cells and is expected to be a potent immunosuppressant and anti-tumor drug. The decrease in lymphocytes and lymphoma cells is mainly the result of FTY720-induced apoptosis. FTY720 directly affects mitochondria and induces cell death. Moreover, FTY720 activates protein phosphatase (PP) 2A and affects anti-apoptotic intracellular signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
3
25
1
Order By: Relevance
“…This explains why a very small amount of PARP cleavage is present in Figure 2C. While this caspase-independent mechanism contrasts with a number of reports, [15][16][17]19,20 caspase-independent cell death has also been reported in chronic lymphocytic leukemia and mantle cell lymphoma. 21,22 FTY720 has been shown to mediate its antimalignant effect through mechanisms other than the binding of its phosphorylated form to the S1P 1 receptor.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tcontrasting
confidence: 45%
“…This explains why a very small amount of PARP cleavage is present in Figure 2C. While this caspase-independent mechanism contrasts with a number of reports, [15][16][17]19,20 caspase-independent cell death has also been reported in chronic lymphocytic leukemia and mantle cell lymphoma. 21,22 FTY720 has been shown to mediate its antimalignant effect through mechanisms other than the binding of its phosphorylated form to the S1P 1 receptor.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tcontrasting
confidence: 45%
“…Diverse pharmacological mechanisms of action were found for FTY720: it can produce cell cycle arrest of lymphocytes (Nagahara et al, 2001), and it can alter production (Yagi et al, 2000), trafficking (Chiba et al, 1998;Brinkmann et al, 2000Brinkmann et al, , 2001Pinschewer et al, 2000), infiltration (Yanagawa et al, 2000), and apoptosis (Enosawa et al, 1996;Bohler at al., 2000;Nagahara et al, 2000) of lymphocytes. Perplexities about FTY720 regarding preclinical and clinical data include that the maximum effects of FTY720 on cell trafficking were achieved at doses smaller than those producing protection This research was supported by Novartis Pharma AG, Basel, Switzerland, and by Grant GM24211 from the National Institute of General Medical Sciences, National Institutes of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also suggested that FTY720 might also promote activation of the serine/threonine phosphatase PP2a. 20,21 Based upon the potential of FTY720 to activate PP2a and recent studies demonstrating FTY720 induced apoptosis in T lymphocytes 20,22,23 and multiple myeloma cell lines, 24 we sought to investigate the in vitro and in vivo activity of this agent in ALL and CLL. Herein, we report that FTY720 has potent in vitro and in vivo activity in a variety of B-cell malignancies and mediates apoptosis in a Bcl-2-and caspaseindependent manner through activation of the serine/threonine phosphatase PP2a.…”
Section: Introductionmentioning
confidence: 99%